Taktik Komunikasi Efektif dalam Kampanye Lingkungan : Peran Humas dalam Kesadaran dan Aksi Bersama - Meyta Indah Hapsari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
In contemporary environmental discourse, the role of Integrated Marketing Communication (IMC) and collaborative efforts between Public Relations (PR) practitioners and environmental experts hold significant relevance. This study explores the pivotal role of communication strategies in environmental campaigns and the collaborative mechanisms between PR and environmental specialists within various organizational contexts. Estaswara (2000) underscores the strategic necessity of integrated communication in marketing, emphasizing its transformation from a mere promotional tool to a strategic business process. The findings highlight the insufficiency of environmental awareness alone in inciting tangible action. Discussions center around designing campaign messages to effectively drive concrete and sustainable behavioral changes. Collaboration between PR and environmental experts is articulated through several methods. Firstly, monitoring emissions involves joint efforts to develop and manage emission monitoring systems like Continuous Industrial Emission Monitoring Information System (CISPEK) and Continuous and Networked Effluent Water Quality Monitoring System (SPARING). Secondly, Performance Rating Program for Environmental Performance (PROPER) is used by PR to establish cooperation and enhance public trust in environmental management. Thirdly, effective communication and community engagement leverage social media and communal activities to disseminate information and amalgamate feedback from the public. The jurnal asserts the vital role of PR in fostering public participation, guiding communities on critical issues, and encouraging their contribution to sustainable development. By providing pertinent explanations, PR elevates societal awareness regarding crucial issues like environmental sustainability, climate change, and public health, stimulating active involvement in sustainable development endeavors..